Social-Aware Spatial Top-k and Skyline Queries. (13th March 2018) - Sohail, Ammar; Cheema, Muhammad Aamir; Taniar, David
Abstract: The widespread proliferation of location-acquisition techniques and GPS -embedded mobile devices have resulted in the generation of geo-tagged data at unprecedented scale and have essentially enhanced the user experience in location-based services associated with social networks. Such location-based social networks allow people to record and share their location and are a rich source of information which can be exploited to study people's various attributes and characteristics to provide various Geo-Social (GS) services. In this paper, we propose two new types of queries called Top-k famous places T k F P and Socio-Spatial Skyline Query S S S Q query, which enrich the semantics of the conventional spatial queries by introducing a social relevance component. In addition, three approaches namely, (1) Social-First, (2) Spatial-First and (3) Hybrid are proposed to efficiently process T k F P and S S S Q queries. Finally, we conduct an extensive evaluation of the proposed schemes using real and synthetic datasets and demonstrate the effectiveness of the proposed approaches.